Initiation of disciplinary action and disciplinary penalty against the employees of higher education institutions in accordance with the Civil Service Regulations Act in Higher Education Institutions - Panomrak , Singha (Journal of Humanities and Social Sciences Loei Rajabhat University, 2023)
By conducting disciplinary actions against employees of higher education institutions currently, the higher education institutions, by virtue of the Institutions Act of the Civil Service Regulations in Higher Education (No. 2) in accordance with Section 56/1, which establish principles for higher education institutions to prescribe rules and procedures for personnel management, discipline and maintenance of discipline, disciplinary action, retirement, appeals and complaints, to be in accordance with the requirements as stipulated in the regulations by the Council of Higher Education Institutions. From the above Act, it can be seen that the conducting of disciplinary actions against employees of higher education institutions, shall be in accordance with the regulations of that higher education institution, but shall not conflict with or contrary to the rules established by the Civil Service Act in Higher Education Institutions; The Civil Service Regulations Act in Higher Education Institutions stipulates that any employee in a higher education institution is accused of Anything with reasonable evidence stating that the disciplinary offense has been committed, or any actions appearing to the supervisor that such employee of particular higher education institution has committed disciplinary offense, the supervisor shall then appoint an investigation committee to that matter Except in the case of non-serious disciplinary offenses or in the case of an apparent offense as determined by the ( Boards of Civil Service in Higher Education Institutions), then an investigation committee may not need to be appointed. Therefore, in case the investigation committee is to be appointed, the institution shall then conduct the investigation to seek the facts if the accused employee of that institution has actually committed any disciplinary offenses or not and is the committed offense of serious or non-serious matter; The measures to be taken during this action is very important, by any chance, if the process is not being carried out properly according to the established rules, or not being carried out at all, or skipping any steps, may result in the conduct being unlawful and will prevent further disciplinary action. Civil Service Regulations in Higher Education Institutions Act (No. 2) B.E. 2551 (2008) Section 56/1 states that determination of position, employment system, recruitment and appointment, wage rate and compensation, additional money and benefits, promotion, changes and transfers of positions, leave, ethics, discipline maintenance and disciplinary action, dismissal, appeals and complaints, and other matters relating to personnel management of employees in higher education institutions are to be done in accordance with the requirements as stipulated in the regulations by the Council of Higher Education Institutions. In case of non-serious disciplinary offenses or in the case of an apparent offense as determined by the (Boards of Civil Service in Higher Education Institutions), the supervisor may consider further disciplinary punishment. In case of disciplinary punishment, The Civil Service Regulations Act in Higher Education Institutions has prescribed 5 disciplinary penalties. 1.Probate 2.Wage cut 3.Wage reduction 4.Disengage 5.Fire. Which will follow the severity of the disciplinary offenses committed by that employee. For non-serious matter, there are 3 disciplinary penalties including 1.Probate 2. Wage cut 3.Wage reduction. For serious matter, there are 2 disciplinary penalties including 1.Disengage 2.Fire